Long-Read Sequencing Identifies the First Retrotransposon Insertion and Resolves Structural Variants Causing Antithrombin Deficiency - de la Morena-Barrio, Belén; Stephens, Jonathan; de la Morena-Barrio, María Eugenia; Stefanucci, Luca; Padilla, José; Miñano, Antonia; Gleadall, Nicholas; García, Juan Luis; López-Fernández, María Fernanda; Morange, Pierre-Emmanuel; Puurunen, Marja; Undas, Anetta; Vidal, Francisco; Raymond, Frances Lucy; Vicente, Vicente; Ouwehand, Willem H.; Corral, Javier; Sanchis-Juan, Alba; NIHR BioResource (Thrombosis and Haemostasis, 2022)
The identification of inherited antithrombin deficiency (ATD) is critical to prevent potentially life-threatening thrombotic events. Causal variants in SERPINC1 are identified for up to 70% of cases, the majority being single-nucleotide variants and indels. The detection and characterization of structural variants (SVs) in ATD remain challenging due to the high number of repetitive elements in SERPINC1. Here, we performed long-read whole-genome sequencing on 10 familial and 9 singleton cases with type I ATD proven by functional and antigen assays, who were selected from a cohort of 340 patients with this rare disorder because genetic analyses were either negative, ambiguous, or not fully characterized. We developed an analysis workflow to identify disease-associated SVs. This approach resolved, independently of its size or type, all eight SVs detected by multiple ligation-dependent probe amplification, and identified for the first time a complex rearrangement previously misclassified as a deletion. Remarkably, we identified the mechanism explaining ATD in 2 out of 11 cases with previous unknown defect: the insertion of a novel 2.4 kb SINE-VNTR-Alu retroelement, which was characterized by de novo assembly and verified by specific polymerase chain reaction amplification and sequencing in the probands and affected relatives. The nucleotide-level resolution achieved for all SVs allowed breakpoint analysis, which revealed repetitive elements and microhomologies supporting a common replication-based mechanism for all the SVs. Our study underscores the utility of long-read sequencing technology as a complementary method to identify, characterize, and unveil the molecular mechanism of disease-causing SVs involved in ATD, and enlarges the catalogue of genetic disorders caused by retrotransposon insertions.
Keywords: long-read sequencing; antithrombin deficiency; structural variants; SVA retrotransposon